Microfinance and Inequality: Case of Indonesia - Leo Indra Wardhana; Fani Pramuditya; Elton Buyung Satriyanto (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
This study aims to investigate the role of microfinance from small-sized banks, usually with a limited geographical area of operation, in Indonesia, namely Bank Perkreditan Rakyat (BPR) on the income inequality. Using a province level panel data of 2012-2018, the results show that loans from such a bank are associated with income inequality reduction, supporting the arguments that microfinance contributes to income inequality reduction. This study provides an indication that micro finance in the form of small-sized bank also have an important role in the financial inclusion, by providing access to finance to micro and small business as well as to the poor that cannot benefit the development of big national commercial banks and capital market. This study has an important policy implication regarding the role of Bank Perkreditan Rakyat in Indonesia.